In Paris or Sofia? Avant-garde poetry and cultural nationalism after devolution - Daniel Williams (Devolutionary Readings: English Language Poetry and Contemporary Wales, 2018)
A predominantly ‘anti-nationalist’ emphasis on ‘hybridity’ and the ‘transnational’ may beseen to characterize much of the poetry and poetic analysis in the period since 1997. Criticshave tended to describe Welsh avant-garde poetry, in particular, in terms that make it antitheticalto cultural nationalism. This chapter responds to the claim that poets have lacked acommitment to the Welsh ‘national project’ since the advent of devolution, and aims to offeran alternative account. I begin by exploring the assumptions and values at work in the currentespousal of ‘hybridity’ before proceeding to argue that in the works of Nerys Williams,Rhys Trimble and Childe Roland we see the distinctive bilingualism and cultural traditionsof Wales being engaged with in ways that are of profound relevance to contemporary debateson Welsh culture, politics and national identity. I am not attempting to corral these writersinto a movement, nor to associate their writings with positions that they may not wish toembrace. My claim, rather, is that the poems discussed in this chapter emerge from a convergenceof poetry and national identity in the period since political devolution; a convergencethat results in the formal and thematic experimentation of avant-garde poetry reconfiguringWelshness, while the distinctiveness of Wales reconfigures the avant-garde.